2002
DOI: 10.1084/jem.20020845
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Outcome of CD40 Signaling Is Dependent on the Duration of CD40 Ligand Expression

Abstract: CD40 ligand (CD154) expression on activated T cells can be separated into an early TCR-dependent phase, which occurs between 0 and 24 h after activation, and a later extended phase, which occurs after 24 h and is reciprocally regulated by the cytokines IL-4 and IL-12. IL-4 represses, whereas IL-12 sustains CD154 expression. Consistent with this, Th1, but not Th2, cells express CD154 for extended periods. Differences in the duration of CD154 expression have important biological consequences because sustained, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
89
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 64 publications
12
89
3
Order By: Relevance
“…6) is in accordance with the CD154 expression found in mouse CD4 T cells, which demonstratedly occurs in two phases (Lee et al 2002). The early phase of CD154 expression occurs within hours of the T-cell activation and is regulated independently of the local cytokine milieu (Lee et al 2002).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…6) is in accordance with the CD154 expression found in mouse CD4 T cells, which demonstratedly occurs in two phases (Lee et al 2002). The early phase of CD154 expression occurs within hours of the T-cell activation and is regulated independently of the local cytokine milieu (Lee et al 2002).…”
Section: Discussionsupporting
confidence: 81%
“…In this phase, the CD154 expression diminishes rapidly and is undetectable within 12-24 h after activation. However, the second phase of CD154 expression occurs between 24 and 72 h and is highly dependent on cytokines (Skov et al 2000;Lee et al 2002;Snyder et al 2007) and costimulatory molecules (Jenkins and Johnson 1993;Kaminski et al 2009), which can sustain CD154 expression for several days.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that the two phases of CD154 expression are differentially regulated; the first stage being responsive to signaling through the TCR and the second phase being modulated by IL-4 and IL-12 cytokines (62). We have yet to analyze CD154 mRNA stability under these different conditions of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that CD40L expression on CD4 Ï© T cells can be separated into an early TCR-dependent phase and a later extended phase, and that the biological outcome of CD40 signaling for B cells depends upon the duration of interaction (27). Interestingly, only Th1 CD4 Ï© T cells exhibit a later extended phase.…”
Section: Endritic Cells (Dcs) 2 Are Believed To Be the Most Potentmentioning
confidence: 99%